Moral Value Consciousness and Equality in Ratnakumar Sambharia’s Stories : रत्नकुमार सांभरिया की कहानियों में नैतिक मूल्य बोध एवं समभाव - Chejara, Yadvendra (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
This article focuses on ethical values and their social impact, including the concept of moral consciousness and its influence on various aspects of society such as social, cultural, religious, political, and economic upliftment. It highlights the importance of ethical principles such as compassion, kindness, altruism, values, and traditions. Furthermore, it demonstrates how issues like casteism, feudal exploitation, and social stereotypes challenge the concepts of ethical values and equality. The article portrays the exploitation and struggles of the Dalit community and other marginalized groups through the stories of Ratnakumar Sambharia. These stories not only raise a voice against social injustice but also establish ethical values and the notion of equality. The author effectively depicts human emotions in the narratives. Abstract in Hindi Language: यह लेख नैतिक मूल्यों और उनके सामाजिक प्रभावों पर केंद्रित है, जिसमें नैतिक चेतना की अवधारणा और उसका समाज के विभिन्न पहलुओं जैसे सामाजिक, सांस्कृतिक, धार्मिक, राजनैतिक और आर्थिक उत्थान पर प्रभाव शामिल है। इसमें नैतिकता के मानदंडों, जैसे दया, करुणा, परोपकार, मूल्य और संस्कारों का महत्व उजागर किया गया है। साथ ही, यह दर्शाया गया है कि जातिवाद, सामंती शोषण, और सामाजिक रूढ़ियों जैसी समस्याएँ नैतिक मूल्यों और समभाव की अवधारणाओं को चुनौती देती हैं। लेख में रत्नकुमार सांभरिया की कहानियों के माध्यम से दलित समुदाय और अन्य कमजोर वर्गों के शोषण और उनके संघर्षों को चित्रित किया गया है। ये कहानियाँ न केवल सामाजिक अन्याय के खिलाफ आवाज उठाती हैं बल्कि नैतिक मूल्य और समभाव को भी स्थापित करती हैं। लेखक मानवीय संवेदनाओं को कहानियों में प्रभावी ढंग से चित्रित करते हैं। Keywords: नैतिक मूल्य, समभाव, सामाजिक न्याय, दलित साहित्य